2003
DOI: 10.2746/042516403776148318
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic mucosal lesions of the arytenoid cartilages of 21 Thoroughbred yearlings: 1997–2001

Abstract: Summary Reasons for performing study: Mucosal ulcers and, occasionally, small granulomas on the axial surface of one or both arytenoid cartilages have been found in TB yearlings presented for post sale endoscopic examination. Objectives: To determine the incidence, endoscopic characteristics and outcome of a group of Thoroughbred yearlings affected with mucosal ulcers and granulomas of the arytenoid cartilage. Hypothesis: The incidence of mucosal ulceration of the arytenoid cartilages of yearling Thoroughbr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 13 publications
1
18
0
Order By: Relevance
“…Ulceration of the mucosa covering the arytenoid cartilages occurs in 0.6% of Thoroughbred weanlings examined after sale (Kelly et al 2003), but its prevalence in racehorses has not to our knowledge been reported. Mucosal ulceration had the highest prevalence (2.4%) of any abnormalities detected in the current study.…”
Section: Prevalence Of Abnormalitiesmentioning
confidence: 82%
See 1 more Smart Citation
“…Ulceration of the mucosa covering the arytenoid cartilages occurs in 0.6% of Thoroughbred weanlings examined after sale (Kelly et al 2003), but its prevalence in racehorses has not to our knowledge been reported. Mucosal ulceration had the highest prevalence (2.4%) of any abnormalities detected in the current study.…”
Section: Prevalence Of Abnormalitiesmentioning
confidence: 82%
“…The clinical importance of mucosal ulceration is uncertain, although in the current study it was not associated with poor race performance. Lesions in 15 of 18 yearling Thoroughbreds with mucosal ulceration detected on endoscopic examination after sale and treated with antimicrobial and anti-inflammatory drugs healed within 42 days (Kelly et al 2003). However, the other 3 horses developed a granuloma at the site of ulceration with one also developing arytenoid chondritis.…”
Section: Prevalence Of Abnormalitiesmentioning
confidence: 99%
“…Histology had a minor impact in the total prevalence of the lesions observed, since only one subepiglottic ulcer not evident grossly was observed on light microscopy. To our knowledge, only 2 studies describe ulcers in the larynx and/or pharynx of racehorses (Kelly et al 2003;Brown et al 2005) but there are none that describe the prevalence of lesions in the subepiglottic area and soft palate free border. In the present study, 7 (54%) of the 13 horses with laryngopharyngeal abnormalities had lesions in the subepiglottic area (subepiglottic ulcers, soft palate kissing lesions and subepiglottic scar), suggesting that an important number of abnormalities may be missed on routine upper airway endoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…There are many reported abnormalities of the upper respiratory tract of Thoroughbred horses observed during endoscopy (Sweeney et al 1991;Hawkins and Tulleners 1994;Hobo et al 1995;Embertson 1998;Stick et al 2001;Kelly et al 2003); however, some anatomical structures in the laryngopharynx (i.e. the subepiglottic region and margins of the intrapharyngeal opening including the free border of the soft palate) are difficult to examine during routine endoscopy and lesions in these locations may be under reported.…”
Section: Introductionmentioning
confidence: 99%
“…The precise aetiology of arytenoid chondritis is unknown, but it is suspected to be secondary to mucosal trauma leading to a viral or bacterial infection that progresses to involve the arytenoid cartilage(s) [1,3]. Haynes et al reported on pathological findings of chondritic arytenoid cartilages following subtotal arytenoidectomy [2].…”
Section: Introductionmentioning
confidence: 99%